Obesity is associated with pain and impaired mobility despite therapy in systemic lupus erythematosus - Borg, Alexander; Lindblom, Julius; Gomez, Alvaro; Soltani, Ameneh; Enman, Yvonne; Heintz, Emelie; Regardt, Malin; Grannas, David; Emamikia, Sharzad; Parodis, Ioannis (Frontiers in Medicine, 2023)
Objective: To investigate whether abnormal BMI is associated with health-related quality of life (HRQoL) impairments, defined as patient-reported problems within the different dimensions of the three-level EQ-5D (EQ-5D-3L), before and after treatment for active systemic lupus erythematosus (SLE).We conducted a post-hoc analysis of data from two phase III clinical trials of belimumab in SLE i.e., BLISS-52 (n=865) and BLISS-76 (n= 819). Underweight was defined as BMI <18.5 kg/m 2 , normal weight as BMI ≥18.5 but <25 kg/m 2 , pre-obesity as BMI ≥25 but <30 kg/m 2 , and obesity as BMI ≥30 kg/m 2 . We investigated associations between BMI groups and problems (level 2 or 3) within each one of the five EQ-5D dimensions before treatment initiation and at week 52, using logistic regression analysis adjusting for age, ethnicity, disease activity, and glucocorticoid dose, and for the post-treatment analysis also for belimumab treatment and baseline EQ-5D-3L responses.Results: Of 1684 patients included, 73 (4%) were classified as underweight, 850 (50%) as normal weight, 438 (26%) as pre-obese, and 323 (19%) as obese. At baseline, obesity was associated with mild to severe problems in all EQ-5D dimensions (P<0.05 for all), yielding the strongest association with problems in mobility (adjusted odds ratio, aOR: 2.1; 95% confidence interval, CI: 1.6-2.8; P<0.001). Pre-obesity was also associated with problems in mobility (aOR: 1.4; 95% CI: 1.1-1.8; P=0.005). Post-2 This is a provisional file, not the final typeset article intervention, obesity was associated with problems in mobility and pain/discomfort, and pre-obesity with problems in mobility and self-care (P<0.05 for all).Conclusions: Our study adds to the evidence that high BMI negatively affects SLE patients' HRQoL, with obesity being associated with pain and impaired mobility despite therapy.